Study of the Level of Mastery of Prayer Skills in Elementary School Students in Bayan District - Sumiadi, Raden (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the level of mastery of prayer skills in grade V Elementary School (SD) students in Bayan District. Prayer skills are basic competencies that must be mastered by every Muslim student, but various reports show that many students still have difficulty in mastering these skills. This study uses a quantitative approach with a descriptive method, involving 180 students from 5 elementary schools spread across five Bayan districts, North Lombok Regency. The sampling technique used stratified random sampling to ensure a balanced representation of various levels of school quality. The results of the study showed that it was known that as many as 131 students or around 73% were already fluent in performing prayers, while the rest, namely 49 students or around 27% were still not fluent. There was no significant difference in prayer ability in upper, middle, and lower schools, indicating that family environment factors and student participation in the Al-Qur'an Education Park (TPQ) had a greater influence. Based on the results of interviews with teachers, limited time for religious learning in schools and lack of direct practice were the main factors in students' low prayer skills. Student participation in TPQ was proven to significantly improve their ability to pray. Therefore, this study recommends improving practice-based learning methods, collaboration between schools and TPQ, and involving parents in guiding children at home. In addition, periodic evaluations are needed by the local government to improve the effectiveness of religious learning in elementary schools.